A tributação não isonômica das instituições financeiras no Brasil - Longo, Sidney Kawamura (2023)
By adopting the exploratory bibliographic method and presenting as its core questioning about the extent of the Union's constitutional competence to establish and increase taxation of financial institutions, this research will observe the institutionalization of the unique situation of banks in the country since its constitution and development to social support for maintenance of state sovereignty and especially the financial emancipation of nations, in this vein, the present study proposes to analyze the differentiated taxation of the financial sector that surplus negatively impacts the ability to promote credit to the productive sectors and the provision of services. This analysis is necessary, as banks have exclusive taxation and i mainly due to the violation of the principle of equality the increase in credit and the curtailment of equity. We highlight the assessment of social security taxation and social contributions on net profits that make up the plot that develops together with the principled elucidations that accompany the reader to the threshold of the research that is limited to the technical verification of the jurisprudence of the Supreme Court of Brazil related to the theme, from the principled perspective of equality and non-confiscation for the verification of fair contributory capacity